Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species - Ravara, Ascensão; Aguado, M. Teresa; Rodrigues, Clara F.; Génio, Luciana; Cunha, Marina R. (European Journal of Taxonomy, 2019)
Five chrysopetalid species are reported from samples collected at bathyal depths in three NE Atlantic regions: the Bay of Biscay, the Horseshoe Abyssal Plain and the Gulf of Cadiz. Arichlidon reyssi (Katzmann et al., 1974), Dysponetus caecus (Langerhans, 1880) and D. profundus Böggemann, 2009 are free-living forms found mainly on biogenic substrates (e.g., coral and sunken wood). A brief description and taxonomical remarks are given for each of these species and their geographical distributions and habitat records were updated accordingly. Natsushima bifurcata Miura & Laubier, 1990 and Craseoschema thyasiricola gen. et sp. nov. are symbionts inhabiting the mantle cavity of chemosynthesis-based bivalves known from four mud volcanoes from the Gulf of Cadiz. Craseoschema thyasiricola gen. et sp. nov. was found inside a thyasirid bivalve and presents mixed morphological characteristics of free-living and symbiotic forms within Calamyzinae Hartmann-Schröder, 1971. A full description of the new species is given together with DNA sequences of the genes COI, 16S and H3 that were used in a phylogenetic analysis to indicate the position of the new genus within the family.